Rainfall erosivity and erodibility of inceptisols in the Southwest Colombian Andes - Ruppenthal, M; Leihner, D.E.; Hilger, TH; Castillo Franco, J.A. (Cambridge University Press, 1996)
The rainfall erosivity (R) and soil erodibility (K) factors of the Universal Soil Loss Equation (USLE) were determined on two sites in the Colombian Cauca Department over a five year period when rainfall was mostly lower than average. The results showed that the high erosion potential of the soils can be attributed more to high rain erosivity than soil erodibility. The R factor explained between 59 and 81% of the variation in soil loss recorded on continuously clean-tilled fallow plots. The erodibility of Inceptisols in the study region is classified as low. Values for soil erodibility (K) ranged from 0.012 to 0.015 (measured in SI units) in the fifth year of permanent bare fallowing. K factors were higher in the rainy than in the dry season. Soils, previously under grass vegetation, were very resistant to erosion in the first two years of bare fallowing. In the third year erodibility increased sharply and continued to increase steadily until the sixth year. K factors predicted by the USLE nomograph underestimated the empirically-determined erodibility of these highly aggregated clay soils.